2022
DOI: 10.1111/bjet.13292
|View full text |Cite
|
Sign up to set email alerts
|

Building personalised homework from a learning analytics based formative assessment: Effect on fifth‐grade students' understanding of fractions

Abstract: This study analyses the potential of a learning analytics (LA) based formative assessment to construct personalised teaching sequences in Mathematics for 5th‐grade primary school students. A total of 127 students from Spanish public schools participated in the study. The quasi‐experimental study was conducted over the course of six sessions, in which both control and experimental groups participated in a teaching sequence based on mathematical problems. In each session, both groups used audience response syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 120 publications
2
7
0
2
Order By: Relevance
“…These results are similar to those obtained in other studies carried out in different academic fields concerning the use of active methodologies in general [57,60], the use of IBL and technology tools within the teaching-learning process in social science disciplines [10,26], and the integration of LA to achieve formative student assessment [6,19,38]. Hence, these findings suggest that this educational approach is beneficial to learning at the tertiary level.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are similar to those obtained in other studies carried out in different academic fields concerning the use of active methodologies in general [57,60], the use of IBL and technology tools within the teaching-learning process in social science disciplines [10,26], and the integration of LA to achieve formative student assessment [6,19,38]. Hence, these findings suggest that this educational approach is beneficial to learning at the tertiary level.…”
Section: Discussionsupporting
confidence: 90%
“…According to Kori et al [37], the presence of technology within the teaching-learning process boosts inquiry learning as it can be harnessed by pre-service teachers to facilitate their solution-finding processes, awareness, and simultaneously afford lecturers-and educators in general-the capability to closely monitor and assess how the learning process is progressing [18,25]. Something that is aligned with the importance of integrating LA to foster both the students' daily and personalised feedback and their formative assessment [5,19,38].…”
Section: Student Ownership and Awareness Of Their Learning Process Th...mentioning
confidence: 99%
“…The authors indicated that learning analytics techniques for unstructured and multimodal student data hold the potential to further assess and elicit students' conceptions. Rodríguez-Martínez et al (2022) developed personalised mathematics homework based on students' responses in online formative assessments and documented that personalised homework generated in this way can boost student comprehension of fractions. These two studies shed light on novel learning analytics approaches that may advance future formative assessment of students' conceptions in different domains.…”
Section: Brief Overview Of Contributionsmentioning
confidence: 99%
“…Se consideraron además estudios sobre el uso de herramientas en el proceso de evaluación formativa (Aguilar & Fernández, 2018;Arévalo et al, 2020;Falcón et al, 2021;Kruit et al, 2020;Ordaz & Acle, 2021;Valverde, 2019) y el uso de herramientas digitales (Bonanzinga et al, 2022;Csapó & Molnár, 2019;Chen et al, 2020;Faber & Visscher, 2018;González-Lerma & Lugo-Silva, 2020;Moreno & Molins, 2021;Rodríguez-Martínez et al, 2022). Se consideran herramientas de diagnóstico como la evaluación de desempeño, utilizada en la evaluación formativa en educación primaria para monitorear el progreso de los estudiantes (Kruit et al, 2020).…”
Section: Figuraunclassified
“…Entre las herramientas digitales utilizadas, se tienen la evaluación formativa automática con retroalimentación interactiva (Bonanzinga et al, 2022); eDia (educativo, digital, interactivo y abierto), diseñada para proporcionar retroalimentación de diagnóstico para profesores y alumnos (Csapó & Molnár, 2019); la pizarra digital interactiva, la cual propicia el interés y la motivación de los alumnos (Chen et al, 2020); Snappet, la cual proporciona retroalimentación a los alumnos y profesores sobre el progreso de las tareas (Faber & Visscher, 2018). Otras herramientas digitales incluyen CLOUDLABS (González-Lerma & Lugo-Silva, 2020), Learning Analytics (Rodríguez-Martínez et al, 2022), AMC Anywhere (Gezer et al, 2021), entre otras. Adicionalmente se encuentra la rúbrica, utilizada como instrumento de evaluación de desempeño tanto para el alumno (Aguilar & Fernández, 2018;Ordaz & Acle, 2021) como para el docente (Arévalo et al, 2020) y futuro docente (Sánchez, 2021), o la evaluación entre pares, en la cual se involucra a los alumnos llevando a cabo la actividad y a su vez realizando la función como evaluador (Gómez et al, 2018;Martín del Pozo & Herrero, 2018;Valverde, 2019).…”
Section: Figuraunclassified